IrO2 modified Crystalline-PdO nanowires based bi-functional electro-catalyst for HOR/HER in acid and base. (May 2022) - Samanta, Rajib; Mishra, Ranjit; Manna, Biplab Kumar; Barman, Sudip
Abstract: Development of active HOR/HER electro-catalyst is crucial for development of next-generation PEM-and-AEM based renewable technologies. Here, IrO2 -modified PdO-nanostructures/carbon-composite with plenty of surface defects was synthesized for HER/HOR applications. The ECSA of IrO2 –PdO/C is found to be 449 m g −1 which is ∼9-fold higher than Pt/C in acid. The HER of IrO2 –PdO/C are 1.15-and 2.35-fold higher than Pt/C in acid and base. The stability test shows excellent stability of this catalyst. It also shows superior HOR activity. The i0, m of IrO2 –PdO/C is ∼647 and 376 mA/mgmetal in acid and base that are 1.78-and 3.63-times higher in compared to commercial Pt/C. Small amount of IrO2 in IrO2 –PdO/C enhances its HOR/HER activity ∼300 times as compared to PdO/C. The IrO2 or defects of the catalyst absorb OHad that reacts with neighboring Had at defect sites or interfaces leading to increase HER/HOR performance through bifunctional mechanism. We demonstrate volcano relationship between exchange current and H∗/OH∗ binding energy confirming that HBE and OHBE are equal descriptors for HOR/HER in base. The HOR/HER in different electrolyte and increasing Li + ions suggests [(H2 O)x -M + -OHad ] in double layer influences the HOR/HER in base. This work could lead to the development of Pt-free electrocatalysts for renewable energy technologies. Graphical abstract: Image 1